PENGARUH METODE PEMBELAJARAN DARING TERHADAP MINAT BELAJAR MAHASISWA PADA MASA COVID 19 - ukti lutvaidah; Prima Pantau Putri Santosa (Jurnal THEOREMS (The Original Research of Mathematics), 2021)
The study was intended to identify the level of interest of students studying at the architecture of the 2 semester university of indraprasta pgri pa and the 20/2021 method used in the study as a qualitative deskntive method. The imi research population is a graduate class of 316 students and it is a class of 80 students. The instruments used in this study are based on a Google form of 20 different question items from 4 comments about the interest of learning which is pleasure, attention, attraction, and involvement in online college. The analysis used in this study USES quantitative data. Research has shown that the level of interest of students studying at the architecture of the university of indraprasta pgri pa has completed its 2020/2021 year in online lectures during the covid 19 pandemic was categorically categorized as well as 75.5%.